PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT THAMRIN BROTHERS KANTOR CABANG BATURAJA 2 - Dyah Ayu Putriani; Angga Wibowo Gultom Wibowo Gultom (Universitas Gorontalo, 2020)
Abstract The purpose of this research is to know the description and effect of organization culture and job satisfaction to the performance of employees at PT. Thamrin Broters Branch Office Baturaja 2. The analysis used is multiple linear regression analysis, t test, F test, and coefficient of determination. The results of the analysis indicate that organizational commitment and job satisfaction on the performance of employees at PT. Thamrin Broters Branch Office Baturaja 2 affect either partially or simultaneously. Results of the analysis of determination (R2) shows that the coefficient of determination (R) organization culture (X1) and job satisfaction (X2) amounted to 60.9% influence on employee performance (Y) while the remaining 39.1% influenced or varied by other variables , Researchers suggest the company in order to remain consistent with the targets to be achieved by employees and implement organizational commitment of employees and improve job satisfaction through the provision of appropriate and fair bonuses so that employees are willing to improve its performance. Keywords: Organization Culture, Job Satisfaction, Employee Performance